Natural biodegradable low-cost Lablab purpureus husk as chromatrap for removal of three hazardous organic cationic dyes from water: Waste to wealth and column elution approach - Sumathi Paramesh; Veerendra Ananthpur; Nagaraju Rajendraprasad (Journal of Water and Environmental Nanotechnology)
Novel results in this study showcase the utilization of sunlight-dried, ground Lablab purpureus husk (LLPh), treated with water and alkali, as a highly efficient bio-adsorbent for the removal of cationic dyes from aqueous solutions. Methylene blue (MB), malachite green (MG), and crystal violet (CV) were effectively adsorbed onto NaOH activated LLPh (NaOH-LLPh) as bio-adsorbent. Employing the Chromatrap method within a column, successfully removed these dyes, while the surface morphology of the bio-adsorbent was elucidated through scanning electron microscopy (SEM) analysis. FTIR spectrometric data revealed valuable insights into the extent of adsorption. The impact of factors including adsorbate concentration, adsorbent dose, pH, contact time, and flow rate on the adsorption process was systematically studied and optimized. Up to 1000 µg/mL of MB and MG, 50 µg/mL of CV were found to be effectively removed by adsorption at pH 4-5, 3 and 2, respectively, at the flow rate of 1 mL/min. The results of kinetic studies and adsorption isotherms of above-mentioned dyes indicates that, all the three dyes follow the pseudo-second order kinetics. The adsorption of MB and MG are well fitted with the Langmuir isotherm model. The other dye CV suits with the Freundlich isotherm model. Based on the results, NaOH-LLPh, as an inexpensive and eco-friendly adsorbent, is suitable for the removal of cationic organic dyes from aqueous samples.